Early Development Survival of Pelophylax Water Frog Progeny is Primarily Affected by Paternal Genomic Input - Doležálková-Kaštánková, Marie; Pyszko, Petr; Choleva, Lukáš (Frontiers in bioscience (Landmark edition), 2022)
BACKGROUND: Hybrid taxa exist in nature, but their fitness can vary greatly. Hybrids are usually thought to have lower viability and survival rate than parental species due to the occurrence of two different genomes and divergent evolution in each species. On the other hand, the hybrid vigour of the F1 generation may give hybrids an advantage in mixed populations where they have to live and compete with parental taxa. Post-zygotic selection with endogenous genetic mechanisms may be a significant evolutionary force in hybrid formation. Here we tested principles of post-zygotic reproductive dynamics in mixed populations of Pelophylax water frogs that would help us understand the origin and maintenance of such systems. METHODS: Within experimental crosses, we combined various diploid Pelophylax genotypes resulting in 211 families. Statistical analysis of progeny was used to measure fertilization success, the rate of embryonic/tadpole mortality and the overall survival of the progeny till the time of metamorphosis. Using Generalized Estimating Equations models and variables defined by a mother/father included in mate pairs, we tested which factor best explains the successful embryonal development. RESULTS: The development of Pelophylax offspring significantly varied in survival rate and morphological malformations. These post-zygotic reproductive dynamics were driven by parental combinations of species pairs. The best values in the proportion of developing eggs, embryos, tadpoles and overall survival showed progeny of homospecific P. lessonae crosses. Total survival rates were relatively similar between L-E and R-E population systems but much lower than homospecific crosses in parental taxa. However, once the early stages passed this period, tadpoles mostly of hybrid hemiclonal origin performed even better than pure P. ridibundus progeny. Hybrid × hybrid crosses showed the highest mortality values. Statistical testing revealed that high mortality affected paternal genetic input. CONCLUSIONS: Combined three water frog taxa and both sexes provided patterns of post-zygotic reproduction dynamics of early development in the widespread population systems in Central Europe. The results further showed high survival rates of hybrid F1s created de novo from parental species despite significant divergence between P. ridibundus and P. lessonae DNA. Potential conservation measures of sexual-asexual systems in natural populations are discussed.
Keywords: hybridizace genetická; Animals; Female; embryogenesis; ženské pohlaví; Genomics; lidé; Ranidae; Hybridization, Genetic; otcové; voda; Water; Male; asexual reproduction; Fathers; mortality; zvířata; mužské pohlaví; hemiclonal; hybridogenesis; genomika; Humans